Prospective Computed Tomographic Analysis of Osteochondral Lesions of the Ankle Joint Associated With Ankle Fractures. (August 2016) - Nosewicz, Tomasz L.; Beerekamp, M. Suzan H.; De Muinck Keizer, Robert-Jan O.; Schepers, Tim; Maas, Mario; Niek van Dijk, C.; Goslings, J. Carel
Background: Osteochondral lesions (OCLs) associated with ankle fracture correlate with unfavorable outcome. The goals of this study were to detect OCLs following ankle fracture, to associate fracture type to OCLs and to investigate whether OCLs affect clinical outcome. Methods: 100 ankle fractures requiring operative treatment were prospectively included (46 men, 54 women; mean age 44 ± 14 years, range 20-77). All ankle fractures (conventional radiography; 71 Weber B, 22 Weber C, 1 Weber A, 4 isolated medial malleolus and 2 isolated posterior malleolus fractures) were treated by open reduction and internal fixation. Multidetector computed tomography (CT) was performed postoperatively. For each OCL, the location, size, and Loomer OCL classification (CT modified Berndt and Harty classification) were determined. The subjective Foot and Ankle Outcome Scoring (FAOS) was used for clinical outcome at 1 year. Results: OCLs were found in 10/100 ankle fractures (10.0%). All OCLs were solitary talar lesions. Four OCLs were located posteromedial, 4 posterolateral, 1 anterolateral, and 1 anteromedial. There were 2 type I OCLs (subchondral compression), 6 type II OCLs (partial, nondisplaced fracture) and 2 type IV OCLs (displaced fracture). Mean OCL size (largest diameter) was 4.4 ± 1.7 mm (range, 1.7 mm to 6.2 mm). Chi-square analysis showed no significant association between ankle fracture type and occurrence of OCLs. OCLs did occur only in Lauge-Hansen stage III/IV ankle fractures. There were no significant differences in FAOS outcome between patients with or without OCLs. Conclusions: Ten percent of investigated ankle fractures had associated OCLs on CT. Although no significant association between fracture type and OCL was found, OCLs only occurred in Lauge-Hansen stage III/IV ankle fractures. With the numbers available, OCLs did not significantly affect clinical outcome at 1 year according to FAOS. Level of Evidence: Level IV, observational study.